Systematic review of melasma treatments: advantages and disadvantages - Sang Ayu Arta Suryantari; Ni Putu Tamara Bidari Sweta; Elvina Veronica; I Gusti Ngurah Bagus Rai Mulya Hartawan; Ni Luh Putu Ratih Vibriyanti Karna (Bali Dermatology Venereology and Aesthetic Journal, 2020)
Background: Melasma is acquired chronic hyperpigmentation mainly affecting women. The pathogenesis of melasma is uncertain, but it is predominantly related to ultraviolet (UV) exposure. Due to its chronic and relapsing nature, melasma is challenging to treat. The currently available treatment often has undesirable side effects and suboptimal results. The treatment principle includes protecting from UV radiation, inhibiting melanin synthesis, and increasing the pathway to remove melanin. Objectives: To define available treatments for melasma and determine advantages and disadvantages, including topical, oral and procedural. Method: Medline, Cochrane library and PubMed databases were searched for articles from January 2011 to June 2020. Only RCTs, comparative, prospective, retrospective and systematic reviews focusing on melasma treatments were extracted, analyzed and discussed. Results: We found 197 studies that met the inclusion and exclusion criteria, with 2314 participants included in this review. The treatments included topical, oral and procedural. In several studies, hydroquinone alone or combination remains the most effective treatment for melasma. Oral and topical tranexamic acid is a beneficial adjuvant treatment in refractory melasma with minimal adverse effects. Procedural treatments such as chemical peels, laser and light-based therapies, and microneedling have mixed and unpredictable results. Overall, the side effects tend to be mild and affect a few of the subjects. Conclusions: The current state of the evidence suggests that some treatments with multiple modalities have their respective advantages and disadvantages. The choice of treatment modality must be adjusted according to the type of melasma, such as its severity, extent and location. A better understanding of melasma through further research may improve the therapy options with the least adverse effects.